2013
DOI: 10.1073/pnas.1216526110
|View full text |Cite
|
Sign up to set email alerts
|

Structure and inhibition of the drug-resistant S31N mutant of the M2 ion channel of influenza A virus

Abstract: The influenza A virus M2 proton channel (A/M2) is the target of the antiviral drugs amantadine and rimantadine, whose use has been discontinued due to widespread drug resistance. Among the handful of drug-resistant mutants, S31N is found in more than 95% of the currently circulating viruses and shows greatly decreased inhibition by amantadine. The discovery of inhibitors of S31N has been hampered by the limited size, polarity, and dynamic nature of its amantadine-binding site. Nevertheless, we have discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
352
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 204 publications
(367 citation statements)
references
References 39 publications
12
352
1
2
Order By: Relevance
“…One, seen primarily at high pH, has been characterized extensively by solution NMR (21,22), solid-state NMR (SSNMR) (10,12), and X-ray crystallography (9). A second form is observed in dynamic equilibrium at lower pH (21)(22)(23), as evidenced by a broadening of magnetic resonances that thus far has made it impractical to determine a high-resolution structure of the protein in this state by SSNMR or solution NMR. X-ray crystallographic studies, however, have provided structures of both states (8,9), which differ primarily in the conformation of the C terminus where protons exit the channel.…”
mentioning
confidence: 99%
“…One, seen primarily at high pH, has been characterized extensively by solution NMR (21,22), solid-state NMR (SSNMR) (10,12), and X-ray crystallography (9). A second form is observed in dynamic equilibrium at lower pH (21)(22)(23), as evidenced by a broadening of magnetic resonances that thus far has made it impractical to determine a high-resolution structure of the protein in this state by SSNMR or solution NMR. X-ray crystallographic studies, however, have provided structures of both states (8,9), which differ primarily in the conformation of the C terminus where protons exit the channel.…”
mentioning
confidence: 99%
“…This conformational transition provides a pathway for proton transfer past the Trp41 gate into the viral interior. In NMR studies at low pH, both conformations are observed in equilibrium with one another (40,43,44 (Fig. S1, Bottom).…”
Section: Significancementioning
confidence: 99%
“…The Inward closed state has also been characterized by solution NMR (39,40) and solid-state NMR (41,42) studies under high pH conditions. The Inward closed conformation can transition to the Inward open conformation by straightening a kink in the TM helix near Gly34 (40,43,44). This conformational transition provides a pathway for proton transfer past the Trp41 gate into the viral interior.…”
Section: Significancementioning
confidence: 99%
“…However, the water dynamics in the AM2 protein probed using 2D infrared (2D-IR) spectroscopy revealed that the well-ordered "ice-like" pore water dynamics at pH 8.0 change to more mobile and "liquid-like" dynamics (on the timescale of a few picoseconds) at pH 3.2 (23). This result suggests an interesting pH-dependent behavior of the AM2 protein that is highly relevant for understanding its PT mechanism.Although many computational studies have investigated the features of AM2 that may influence its PT in recent years (12,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), only a few have explicitly simulated any aspect of the explicit PT process (24,25,29,37,38). This is because it is challenging to accurately model the charge delocalization and Grotthuss shuttling of the hydrated excess proton in a computationally tractable way.…”
mentioning
confidence: 99%